Role of Glucagon and Its Receptor in the Pathogenesis of Diabetes - Jia, Yunbo; Liu, Yang; Feng, Linlin; Sun, Siyu; Sun, Guangwei (Frontiers in Endocrinology, 2022)
Various theories for the hormonal basis of diabetes have been proposed and debated over the past few decades. Insulin insufficiency was previously regarded as the only hormone deficiency directly leading to metabolic disorders associated with diabetes. Although glucagon and its receptor are ignored in this framework, an increasing number of studies have shown that they play essential roles in the development and progression of diabetes. However, the molecular mechanisms underlying the effects of glucagon are still not clear. In this review, recent research on the mechanisms by which glucagon and its receptor contribute to the pathogenesis of diabetes as well as correlations between GCGR mutation rates in populations and the occurrence of diabetes are summarized. Furthermore, we summarize how recent research clearly establishes glucagon as a potential therapeutic target for diabetes.